EFFICACY OF UPADACITINIB IN PATIENTS PREVIOUSLY TREATED WITH TOFACITINIB FOR THE MANAGEMENT OF ULCERATIVE COLITIS. (26th January 2023) - Radcliffe, Marlana; Long, Millie; Barnes, Edward; Herfarth, Hans; Hansen, Jonathan; Jain, Animesh
Abstract: BACKGROUND: Tofactinib is a JAK inhibitor that targets mainly JAK 1 and JAK3 approved to treat Ulcerative Colitis (UC) in 2018. The JAK inhibitor Upadacitinib (upa) was recently approved to treat UC in March 2022 and has increased selectivity for JAK1. The relative efficacy and safety of these two JAK inhibitors is not presently clear. An important clinical question is whether patients who have not responded or lost response to tofacitinib will have a reasonable likelihood of response with upadacitinib. AIM: To determine whether patients previously exposed to tofacitinib would benefit from treatment with upa. METHODS: We identified adult patients at our center with active UC who had previously been treated with tofacitinib who were started on upa in the spring of 2022. Pre- and post- upa characteristics were recorded including demographic information, prior treatments, hemoglobin (hgb), albumin (alb), C-reactive protein (CRP), and partial Mayo score (pMS). Primary end points evaluated were clinical response (decrease in pMS > 2), and clinical remission (pMS < 2). Secondary endpoints included serious adverse events, steroid use at time of follow up, and normalization of CRP, hgb and alb. IRB approval was obtained for the study. RESULTS: A total of 3 patients were identified. All patients were given upa 45 mg daily for 8 weeks followed by 30 mg daily for maintenance. Median follow up time was 10 weeks (range 10-11 weeks). All three patients achieved the primary endpoints of clinical response and remission with pMS values of 0 at time of follow up. Patients 1 and 2 were concurrently started on a prednisone taper when initiating upa and were no longer on prednisone at time of follow up. Patients 1 and 2 had normalization of their CRP values, patient 3 only had a pre-upa CRP value available and that was 0. See table 1 for data on hgb and alb levels. Patient 1 had a pre-upa endoscopic mayo score of 3, while patients 2 and 3 had pre-upa endoscopic mayo scores of 2. No patient had post-upa endoscopic evaluation at time of follow up. No patient had any serious adverse events. CONCLUSIONS: In this small case-series, use of upadacitinib in patients previously treated with tofacitinib was safe and effective in achieving clinical remission.